Social Parasitism as a Form of Deviant Behavior (Eurasian Research Bulletin, 2023)
The problem of social dependency and parasitism practices prevalence in the modern society is acknowledged as one of the urgent problems both by the specialists of social sphere and researchers. The obviousness of social dependency as the social problem demanding effective efforts to solve it determines the existence of scientific problem, which consists in the limited knowledge of the causes and factors generating and supporting this phenomenon. The analysis of existing research works on this topic shows that most of them are of descriptive and stating character.